Early Childhood Education at the Intersection of East and West: An Analysis of Curriculum Shifts in Indonesia and Turkey - Hidayati, Zuhriyyah; Kusaeri, Kusaeri; Rusydiyah, Evi Fatimatur (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The early childhood education curriculum in the past few decades has undergone reforms and orientation shifts along with the shift in the orientation of the education curriculum in general. This article aims to analyze the shift in early childhood education curriculum between Indonesia and Turkey by a comparative method. The method used in this study is a systematic literature review review which starts from the process of literature search, screening and feasibility test. The results of this study found that there is a similarity in the shift in the early childhood education curriculum in Indonesia and Turkey, namely the trend of more research on learning methods and assessments than research on learning objectives and content. This is due to a shift in the global trend in the orientation of the educational curriculum in general, namely from content-based-curriculum to outcome-based-curriculum, from forward design to backward design. This finding shows the need for adjustments for educators and stakeholders in early childhood education so that the educational process runs in accordance with the demands of the times